A Case Report on 11 Weeks Miscarriage in a 32 Years Pregnant Women Due to Rubella Virus - Pamu, Sagar; Varikuti, Shravani; Thakkalapally, Lakshmi; Chalimila, Sahirmayi (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
A rare case was founded in Hyderabad with a problem of miscarriage in 11 weeks pregnant women aged 32 years due to an attack of rubella virus. She came to hospital with a chief complaints runny nose, fever, headache, and joint pains from last 10 days and mild rashes over skin from last 5 days. Although she was under good diet and medication with folic acid and ferrous ascorbate she suffered from her chief complaints. Her blood reports were found to be normal, but ultrasound scan reported with no heartbeats of fetus and confirmed as miscarriage. To know its cause patient was suggested to blood serum test by Enzyme Immunoassay method and it reveals presence of IgM. So it was confirmed as an attack with rubella virus and done voluntary abortion. Later she was treated for her symptoms with acetaminophen and ibuprofen and also vaccinated with rubella vaccine.